Catalytic thermochemical cracking of polyethylene over nanocomposite bentonite clay. Issue 1 (February 2021) - Hamouda, A S; Acharjee, P; Abdelrahman, A; Radwan, A M; Zaki, A H; Farghali, A; Mohamed, H F M; Yadav, A; Bhatnagar, A; Goel, A
Abstract: Catalytic thermochemical cracking of polyethylene has been investigated in presence of a series of bentonite clay based nanocomposite with a view toward assessing their suitability in a process for converting plastic waste to fuel. Metal oxides such as manganese oxide (MnO), titanium oxide (TiO2 ) and zinc oxide (ZnO) were impregnated with sodium montomorillonite bentonite. The clay catalysts were characterized by x-ray diffraction (XRD), scan electron microscope (SEM), transmission electron microscope (TEM) and energy dispersive x-ray (EDX) spectrometers. The effect of different catalysts on the composition and the yield of gaseous was evaluated. ZnO nanocomposite bentonite clay achieved the highest methane gas formation around 93%. The superior catalytic performance of nanocomposites is probably attributed to their uniform dispersed of oxides particles on montmorillonite support.